Evaporative performance of Single Tube and Multi Tube Falling Film Evaporator Prototypes for Molten Butter: An Experimental Study - Wale, Gaurav S; Barnwal, Pradyuman; Deep, Ankit; Barge, Rahul S (Indian Journal of Dairy Science, 2019)
This paper presents experimental evaluation of evaporative performance of single tube and multi-tube falling film evaporator prototypes for moisture evaporation from molten butter. For single tube falling film evaporator, steam pressures (1.9 kgf/cm², 2.3 kgf/cm², and 2.8 kgf/cm²) and film thicknesses (2 mm, 3 mm and 4 mm) were varied for evaporative performance i.e. steam economy, specific steam consumption, evaporation rate and evaporation ratio. The performance parameters were found statistically significant (p≤0.05) for film thickness and steam pressure and their interactions. The average steam economy (1.75 to 1.80) and evaporation rate (0.18 to 0.21 kg/min) was highest whereas average evaporation ratio (0.83 to 0.86) was lowest for 2 mm film thickness for the studied steam pressures. For multi-tube falling film evaporator, having five tubes in one shell, steam pressure and pump speed were varied for evaporative performance on molten butter. For studied steam pressures, evaporative performance parameters were statistically significant (p≤0.05). For pump speed, evaporation rate and evaporation ratio were statistically significant whereas steam economy and specific steam consumption were statistically non-significant (p≤0.05). At 2.8 kgf/cm2 steam pressure and 320 rpm pump speed, highest steam economy and evaporation rate whereas lowest specific steam consumption and evaporation ratio were obtained. It was observed that falling film phenomena may be used for butter oil making with some improvements.